Hedonic and Proximate Analysis of Parang-parang Fish Bone Crackers and Moringa Leaves as an Alternative Food for Stunting Prevention - Eri Virmando; Hamdani SP Ginting; Emilia Emilia; Ambar Wicaksono; Retno Febrianti (Sarana Ilmu Indonesia (Salnesia), 2026)
Fish bones are a potential waste containing micronutrients, but their use in food products is still limited. Fortification of moringa leaf powder has the potential to improve the nutritional quality of food products. This study aimed to increase the nutritional value of parang-parang fish bone crackers (Chirocentrus dorab) added with moringa leaf flour (Moringa oleifera) as a food alternative that has the potential to support stunting prevention. The type of pure experimental research used was a Completely Randomized Design (CRD) with two replications. The treatment of parang-parang fish bone crackers and moringa leaf flour formulations was 3 levels, namely F1 = 75%, 25%, 1%, F2 = 75%, 25%, 3%, and F3 = 75%, 25%, 5%. The organoleptic test involved 30 trained panelists to assess the preference for fish cracker products, including color, aroma, texture, and overall. Then, an analysis of the nutritional content was also carried out, which included energy, protein, fat, carbohydrates, phosphorus, and calcium in the product. Analysis using nonparametric statistical tests, Kruskal-Wallis and Mann-Whitney, a p-value <0.05 was considered significant. The study showed that the formula (F1) was most preferred by panelists in all organoleptic parameters. Meanwhile, the results of the proximate test showed the highest energy (440.44 kcal) and fat (14%) in F3, protein (4.36%), calcium (1125.53 mg), phosphorus (5397.44 mg), ash content (6.88%), and water content (1.63%) were highest in F2, while the highest carbohydrate content was found in F1 (78.85%). Formula F1 was most preferred with a significant difference, while F2 has the potential to be the best choice to increase protein, calcium, and phosphorus content, so that it can be developed as a functional food in efforts to prevent stunting.